Effect of Pallas herbicide residue on stimulating the pathogenicity of Alternaria alternata in causing leaf spot in cowpea plant - AL-Waeli, Muhannad; Merjan, Ali (University of Thi-Qar Journal of agricultural research, 2024)
Summary:This study was carried out to spotlight on the effect of Pallas herbicide residues of isolates of Alternaria alternata in increasing their pathogenicity and stimulating them to cause symptoms of cowpea leaf spot in deferent region of Babylon Governorate, Iraq.The results of pathogenicity test using radish seeds revealed the ability of three isolates of Alternaria alternata to reduce the percentage of radish seeds germination significantly compared with control treatment. The results showed that the development of the inoculum for the tested isolates on a nutrient medium that was previously prepared with 5 ppm of the herbicide Pallas has contributed to increasing the pathogenicity of these isolates by significantly reducing the percentage of cowpea seeds by following the blotting paper folds technique, Similar results were obtained after supplementation the liquid medium of fungal isolates with 5 ppm of the herbicide Pallas in studying liquid fungal infiltrates in cowpea seedlings infection.          The results of the greenhouse were confirmed with laboratory experiments results, The concentration of 5 ppm of the herbicide Pallas had a significant effect on increasing the pathogenicity of isolates of the fungus Alternaria alternata. These pathogens significantly reduced the percentage of germination of cowpea seeds in the potting soil, and reduced the heights of infected plants and significantly reduced dry weight compared to the control treatment. Increasing the appearance of leaf spot symptoms on true leaves of cowpea plants treated with sporophyte suspension prepared with 5 ppm of Pallas herbicide.